2018
DOI: 10.1016/j.physbeh.2017.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the links between early life and young adulthood social experiences and men's later life psychobiology as fathers

Abstract: Early life cues of environmental harshness and unpredictability have been hypothesized to influence within-species variation in the timing of life history transitions and the dynamics of reproductive strategies, such as investments in mating and parenting. It is also believed that adolesence is an influential developmental period for male reproductive strategies, with those who achieve greater social and sexual success during that period maintaining faster life history strategies into adulthood. If correct, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Fathers provide critical investments, including food, protection, instruction and direct care. Comparing relative impacts of different types of paternal investments and measuring hormonal correlates of paternal investment is a growing area of research [9, 10, 12, 14]. Following a major 2014 flood, we find that greater crop losses are associated with lower levels of male testosterone, consistent with parallel literatures addressing physiology of the stress response and parenting.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Fathers provide critical investments, including food, protection, instruction and direct care. Comparing relative impacts of different types of paternal investments and measuring hormonal correlates of paternal investment is a growing area of research [9, 10, 12, 14]. Following a major 2014 flood, we find that greater crop losses are associated with lower levels of male testosterone, consistent with parallel literatures addressing physiology of the stress response and parenting.…”
Section: Discussionsupporting
confidence: 80%
“…Testosterone is associated with paternal investment in humans and other primates [812], and its relationship to family stress, including crop loss and family illness and injury, is of interest to the growing field of research examining the physiology of parenting. New methods of quantifying male physiological investment using hormonal activity have recently become possible, providing insight into individual-level variation in men’s responses to young children [8, 13, 14]. Relevant studies show that high-investing fathers have lower levels of testosterone than lower-investing fathers [10, 14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Sarma et al. (2018) found that new fathers who experienced early life unpredictability showed attenuated declines in T across a 4.5‐year study period—perhaps evidence that maintaining elevated T is indicative of a more mating‐oriented (over parenting) strategy. Our own work (Corpuz & Bugental, 2020) demonstrated that the timing of a male’s sexual development predicted the magnitude of his postnatal T rebound.…”
Section: Discussionmentioning
confidence: 99%